Freeze-drying encapsulation of red wine polyphenols in an amorphous matrix of maltodextrin - Sánchez, Virginia Estela (2013)
Fil: Sánchez, Virginia Estela. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina